Life Cycle Assessment as a Tool of Environmental Safety in Car Recycling - Milan Majernik; Jana Chovancova; Imrich Fekete (Communications - Scientific letters of the University of Zilina, 2008)
Numerous and wide-ranging initiatives are being pursued all over the world today to help pass on a sound natural environment to future generations. Automotive production is one of Slovakian leading industries. Because of urgent priority on protecting the environment, it is inevitable for manufacturers to be engaged in ongoing efforts to develop more environmentally friendly automobiles and a more viable infrastructure for them – one in which provisions for environmental protection, including recycling, constitute an essential part. The Life Cycle Assessment (LCA) is atool for the systematic evaluation of the environmental aspects of aproduct or service system through all stages of its life cycle. The article is focused on some possibilities of improving the environmental safety of motor vehicles especially by application of the LCA in automobile production.